Study on the Incineration Process of Food Wastewater in the Demo-Scale Stoker System - Park, Hyun-Seo; Gyu Kim, Cheol; Hwang, Seung-Min (Asian Journal of Chemistry, 2012)
The demo-scale stoker system is used at incineration facilities and the scheme on incineration treatment of the food wastewater emitted from food recycling facilities into municipal waste incinerators was investigated. The ammonia component in the food wastewater functions as the reductant in selective non-catalyst reduction. Remarkable reduction of nitrogen oxide is achieved by using food wastewater containing plenty of the NH3 component. The 26 items of air pollution matter, that is, nitrogen oxide (NOx), sulfur oxide (SOx) and dioxin etc. are measured while incinerating food wastewater and it is found that they all are under the value of allowable exhausts, by allowable exhaust standards. In case of the food wastewater, it can be confirmed that the furnace wall is kept in the unsoiled condition of the refractory surface by a coating effect, according to the spray of the food wastewater. Furthermore, it is found that the fly ash is combusted completely and the outer wall of the water pipe is in a satisfactory state owing to keeping it at 870-950 ºC of the second combustion temperature in order to spray the food wastewater.